A key factor of translation reinitiation, ribosomal protein L24, is involved in gynoecium development in Arabidopsis. (1st August 2004) - Nishimura, T.; Wada, T.; Okada, K.
Abstract : In polycistronic genes, uORFs (upstream open reading frames) within the 5′-transcript leader sequence of major ORFs may regulate the translation of these major ORFs. In this case, ribosome reinitiates translation at a start codon of downstream ORF after translation termination of uORF. The plant RPL24 (ribosomal protein L24) is a key factor for translation reinitiation of downstream ORFs on the polycistronic cauliflower mosaic virus 35S RNA transcription unit. In the RPL24-deficient mutant of Arabidopsis, short valve ( stv ), the basal region of the ovary is shortened, whereas the gynophore appears elongated. This phenotype is never seen in known mutants of other ribosomal protein genes, suggesting that RPL24 has a specific role in gynoecium development. Similar phenotypes were observed in the ett ( ettin ) and mp ( monopteros ) mutants. Both ETT and MP genes possess uORFs. We examined the hypothesis that these uORFs regulate their downstream major ORFs by a transient expression assay in Arabidopsis mesophyll protoplasts. Our results supported the idea, suggesting that the structural defects of the gynoecium in stv mutants were caused by decreased efficiency of translation reinitiation of ETT and/or MP .